Endoscopic resection of rectal neuroendocrine tumors: zero disease-related deaths during a 10-year follow-up period - Yasuyo Hayashi; Haruei Ogino; Yosuke Minoda; Yoshimasa Tanaka; Yoshitaka Hata; Masaru Kubokawa; Seiichiro Sakisaka; Kazuhiro Haraguchi; Shin-ichiro Fukuda; Soichi Itaba; Daisuke Yoshimura; Shunsuke Takahashi; et al. (BMC Gastroenterology)
Abstract Background Gastrointestinal neuroendocrine tumors (GI-NETs) are slow-growing tumors with the potential for malignancy that originate from neuroendocrine cells. Therefore, early diagnosis and treatment of GI-NETs are necessary to prevent metastasis. The widespread use of colonoscopy, which allows early detection of rectal neuroendocrine tumors (rNETs) that are small enough to be treated endoscopically, has resulted in an increasing rate of endoscopic resection of rNETs. However, whether the long-term prognosis of endoscopically resected rNETs is favorable has not yet been determined. This study aimed to assess whether endoscopically resected rNETs affect the long-term prognosis of patients. Methods We retrospectively reviewed the medical records of 163 consecutive patients with rNETs who underwent endoscopic resection at 11 hospitals in Japan between 1999 and 2012. The primary analysis focused on 47 patients with 51 rNETs who underwent ≥ 10 years of follow-up. The secondary analysis focused on patients who underwent less than 10 years of follow-up. Results The median follow-up period of patients included in the primary analysis was 12.3 years (range, 10–19.1 years). The median lesion size was 5 mm (range, 2–12). Three lesions were treated using conventional endoscopic mucosal resection (EMR). Twenty-nine lesions were treated using modified EMR. Nineteen lesions were treated using endoscopic submucosal dissection. The R1 resection rate and lymphovascular invasion rate were 15.7% and 25.5%, respectively. The curative resection (CR) rate and non-CR rate were 66.7% and 33.3%, respectively. Two patients with lesions treated with non-CR underwent radical surgery. None of the 47 patients experienced lesion recurrence during the 10-year follow-up period. Two patients whose lesions were treated with CR died of other diseases. Conclusions Death attributable to rNETs did not occur among patients who underwent at least 10 years of follow-up after endoscopic resection.